Keragaan 23 Varietas Jagung Manis (Zea mays saccharata. Sturt) Komersial - Ridho Radiyan Gunawan; Dwiwanti Sulistyowati; Arya Widura Ritonga; Endang Krisnawati; Bayu Adirianto (Jurnal Agroekoteknologi, 2022)
Performance is one of the important stages in breeding sweet corn before releasing varieties. Performance evaluation is carried out to determine the phenotypic character of a genotype so that the yield potential of a variety can be known. Research on the performance of sweet corn in Indonesia is still relatively rare, so this research needs to be carried out with the aim of knowing the performance and yield of 23 commercial sweet corn varieties (Zea mays saccharata Sturt) in Indonesia. The study was carried out at the Leuwikopo Experimental Garden, Dramaga, Bogor from August to November 2021 using one factor, namely varieties with a complete randomized group design with three replications. The results of analysis of variance on 23 varieties of sweet corn showed that the genotype had a very significant effect on the characters of plant height, cob height, age of female flower emergence, anthesis silking interval, cob length, sweetness level, shelf life and cob weight, both with and without husks. weight per plot, and sweet corn crop productivity. In addition, the genotype had a significant effect on the length of the cob stalk and had no significant effect on the character of the stem diameter, the diameter of the cob, and the length of the seed cob. The varieties with the best productivity were found in the Talenta variety. In addition, observations of each observed character indicate the advantages and disadvantages of the tested varieties.Keywords: genotype, yield, character, performance, productivity